Study of the effect of pretreatments on the germination and growth of Pistacia Atlantica subsp. atlantica: Investigations for the conservation of an endangered species in Morocco - Bassouya Mohammed; Jawhari Fatima Zahra; Lafraxo Soufyane; Chedadi Mohamed; Bari Amina (BIO Web of Conferences, 2024)
The study delves into the critical issue of declining Moroccan endemic plant species of agro-sylva-pastoral and medicinal significance, impacted by various environmental degradation factors. With the aim of conserving and rehabilitating these species, the research focused on improving the germination and growth parameters of Pistacia atlantica subsp. atantica whose seeds were carried from different area of the Middle Moulouya; Oled Ali Youssef; El Orjane and Fritissa. In this study, nine different treatments were employed to overcome seed dormancy. These treatments included chemical scarification using gibberellic acid and sulfuric acid (98%), thermal scarification at 40°C for 24, 48, and 72 hours, mechanical scarification using manual sandpaper, and stratification at +4°C for 45, 60, and 75 days. The results showed that mechanical scarification yielded notably higher germination rates compared to the control group. Specifically, for seeds from Oled Ali Youssef, the germination rate was 81.11%, while for El Orjane and Fritissa, it was 38.88% and 71.11%, respectively, in contrast to 67.78%, 25.56%, and 44.44% in the control group. Moreover, the study revealed that treatments such as mechanical scarification, gibberellin application, and 30-day cold stratification significantly influenced the growth of seedlings, enhancing propagation practices for the species from its seeds. These findings underscore the importance of seed source, viability, and pre-germination treatments in achieving successful germination and growth.